Polar metal phase stabilized in strained La-doped BaTiO3films - Takahashi, K. S.; Matsubara, Y.; Bahramy, M. S.; Ogawa, N.; Hashizume, D.; Tokura, Y.; Kawasaki, M. (Scientific reports, 2017)
Ferroelectric polarization and metallic conduction are two seemingly irreconcilable properties that cannot normally coexist in a single system, as the latter tends to screen the former. Polar metals, however, defy this rule and have thus attracted considerable attention as a new class of ferroelectrics exhibiting novel properties. Here, we fabricate a new polar metal film based on the typical ferroelectric material BaTiO 3 by combining chemical doping and epitaxial strain induced by a substrate. The temperature dependences of the c -axis lattice constant and the second harmonic generation intensity of La-doped BaTiO 3 films indicate the existence of polar transitions. In addition, through La doping, films become metallic at the polar phase, and metallicity enhancement at the polar state occurs in low-La-doped films. This intriguing behaviour is effectively explained by our first-principles calculations. Our demonstration suggests that the carrier doping to ferroelectric material with epitaxial strain serves as a new way to explore polar metals.